Progress and Challenges of Service Delivery in South Africa Since 1994 - Hanyane, Barry; Naidoo, Goonasagree (Mediterranean Journal of Social Sciences, 2012)
The new South Africa came into existence in 1994. The incoming government faced amassive task of fiscal, political, social and economic transformation, all of which wouldrequire an effective public service capability. Yet the public service itself had been subjectduring the Apartheid era to the same limitations as other key South African institutions.Due to the lack of know how in 1994, South Africa needed an overwhelmingtransformation of public service focus, culture and procedures. Yet, 15 years after thedemocratic dispensation’s arrival, many people still lack access to the most basic ofnecessities. Woolard (2002) in Burger (2005:483) argues that it is visible that poverty isSouth Africa’s priority as it is estimated that approximately 37% of South Africanhouseholds , and probably more today, survive on less than R1 000 in a month.